Ecophysiological Responses of Five Mangrove Species (Bruguiera gymnorrhiza, Rhizophora stylosa, Aegiceras corniculatum, Avicennia marina, and Kandelia obovata) to Chilling Stress - Wang, Shu-Min; Wang, You-Shao; Su, Bo-Yu; Zhou, Yue-Yue; Chang, Li-Fang; Ma, Xiao-Yu; Li, Xiao-Mei (Frontiers in Marine Science, 2022)
Although the low temperature is a critical growth constraint on plants, the physiological mechanism remains unclear, especially in mangrove plants. Hence, the morphological characteristics of five mangrove plants (Bruguiera gymnorrhiza, Rhizophora stylosa, Aegiceras corniculatum, Avicennia marina, and Kandelia obovata) were compared under chilling stress. The contents of hydrogen peroxide (H2O2), malondialdehyde (MDA), and proline were tested. Activities of reactive oxygen species (ROS)-scavenging enzyme [superoxide dismutase (SOD), peroxidase (POD), and catalase (CAT)] were also measured after chilling stress. It was concluded that K. obovata can well tolerate chilling stress, and B. gymnorrhiza suffered the most severe chilling damage. Leaf-morphology observation exhibited that K. obovata and A. corniculatum can sustain chilling stress, while B. gymnorrhiza wilted and A. marina turned brown. The content of H2O2 increased at first and subsequently decreased in all plants. MDA increased instantaneously in B. gymnorrhiza and R. stylosa but changed slowly in K. obovata and A. corniculatum. The high content of proline accumulated in B. gymnorrhiza and K. obovata. The activities of the SOD, POD, and CAT increased at first and then decreased in all mangrove species. The antioxidants maintained high activity in K. obovata while decreasing earliest in A. marina exposed to the long-term chilling stress. Principal component analysis (PCA) indicated that high antioxidant enzyme activities play key roles in chilling tolerance for mangrove plants. The longer-term chilling tolerance of K. obovata may be related to the high antioxidant enzyme activities and proline accumulation. Lower H2O2 and MDA contents strengthen the anti-chilling ability of A. corniculatum. Further investigation on the molecular mechanisms will facilitate the understanding of the anti-chilling ability of mangrove plants.